(untitled) (Biological Sciences - PJSIR, 1995)
Characteristic fragment ions obtained in FABmass spectrometry of ribose alkylated cytidine S’-monophosphate (S’-CMP) derivatives ill the negative mode are described. All the compounds examined exhibited either molecular ion M or quasimolecular ion M·H, the fragment ions can be used to characterise these nucIeotides.